The influence of OGV airfoil profile on the TRF. (August 2019) - Li, Shulei; Jin, Donghai; Gui, Xingmin; Li, Jinwei
Abstract: The outlet guide vane in a turbine rare frame plays a vital role in de-swirling the flow as well as load-bearing. This paper numerically simulates the performance of the single stage turbine with different airfoil profile design in the outlet guide vane. The result shows that the outlet guide vane with NACA65 profile has the best performance. The pressure growth in the suction side is steady and no obvious separation is found in the flow field.